(untitled) (International Research Journal of MMC, 2021)
Government can apply learning continuity plan followed by private school during the lockdown period in the context of Covid-19 which appears as outbreak from Wuhan, China and spread rapidly all over the world. Since education is the systematic process of getting or receiving knowledge in the institutions, privatization of education is also being accepted by many countries and have brought the policy to emerge the education sector with the help of public and private schools. In the present context, when the Corona virus spread rapidly all over the world, WHO initiates to stay safe in quarantines and UNESCO suggest about closures of schools and universities. In this context, a study was conducted in 8 schools of every province of Nepal with Kathmandu valley. Schools were chosen randomly as well as mixed method was used to analyze the study. Chi-square, cross tabulation and correlation analysis was done to elaborate the data and SPSS vol-20 was used to interpret the data. In Nepal, private schools of urban area and some public schools are playing an effective role in continuing education through online learning constructing digital infrastructure. However, the majority of private schools are found less effective in online class due to geographic and socioeconomic conditions as well as they are facing electricity and internet problems to continue education in this pandemic era. So, government as well as private sector should prepare Temporary Learning Centre (TLC) and bring the Learning Continuity Plan (LCP) to urban and rural areas to continue education in the COVID -19 periods.